1996
DOI: 10.1002/adma.19960080820
|View full text |Cite
|
Sign up to set email alerts
|

Turning down the heat on semiconductor growth: Solution‐chemical syntheses and the solution‐liquid‐solid mechanism

Abstract: Semiconductor crystal growth at low temperatures and under mild reaction conditions would usher in a technological revolution. Following a brief discussion of the processes that occur during crystal growth, several growth techniques are described, including electrodeposition and surfactant‐interface growth. Particular attention is paid to solution–liquid–solid growth, a technique discovered by the authors that resembles a living polymerization and a phase transfer reaction, by which crystalline III—V materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Various methods have been developed to synthesize 1-D nanomaterials (Klein et al 1993;Dai et al 1995;Morales and Lieber 1998;Pan et al 2001). In contrast, the solution approaches have been proved to provide an alternative route for the synthesis of 1-D nanomaterials (Buhro et al 1996;Holmes et al 2000;Peng et al 2000;Peng 2001, 2002). The template method is known to be a very effective method for the fabrication of the desired materials (Torigoe and Esumi 1995;Nagappa et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Various methods have been developed to synthesize 1-D nanomaterials (Klein et al 1993;Dai et al 1995;Morales and Lieber 1998;Pan et al 2001). In contrast, the solution approaches have been proved to provide an alternative route for the synthesis of 1-D nanomaterials (Buhro et al 1996;Holmes et al 2000;Peng et al 2000;Peng 2001, 2002). The template method is known to be a very effective method for the fabrication of the desired materials (Torigoe and Esumi 1995;Nagappa et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Generally, one dimensional nanostructures can be fabricated by template directed growth methods such as using carbon nanotubes [11,12], porous aluminum templates [13,14], the vapor liquid solid (VLS) [15][16][17] and the vapor solid (VS) mechanisms [18]. Solution approaches have also been explored for the synthesis of one dimensional nanostructures [8,[19][20][21][22]. Previous work has shown that the solvothermal/hydrothermal process is a versatile route for the synthesis of various semiconductors nanorods [23], lanthanide hydroxide nanorods [24] and thin tellurium nanobelts/tubes [25].…”
Section: Introductionmentioning
confidence: 99%
“…), and the reaction was usually initiated under mild conditions or under natural conditions to turn down the heat for the synthesis of materials. [68,69] Recent advances in soft synthesis of diverse nanomaterials have demonstrated that soft approaches are indeed promising for controllable synthesis of low dimensional nanostructures such as one-dimensional (1D) nanostructures of chalcogens and chalcogenides, [70] and inorganic nanotubes. [71] In this Feature Article, we highlight the latest development and emerging new synthesis solution strategies for the syntheses of II-VI semiconducting nanomaterials and inorganic-organic hybrids semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%